Unemployment, market work and household production - Michael C. Burda; Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2009)
Using time-diary data from four countries we show that the unemployed spend most of the time not working for pay in additional leisure and personal maintenance, not in increased household production. There is no relation between unemployment duration and the split of time between household production and leisure. U.S. data for 2003-2006 show that almost none of the lower amount of market work in areas of long-term high unemployment is offset by additional household production. In contrast, in those areas where unemployment has risen cyclically reduced market work is made up almost entirely by additional time spent in household production.
urn:nbn:de:101:1-20090209259
Keywords: E24; J22; D13; 330; Unemployment; time use; household production; paid work; Arbeitslosigkeit; Zeitallokation; Haushaltsproduktion; Hausarbeit; Zeitbudgetforschung; USA